Social and economic analysis of the demand for public transport in Vilnius - Griškevičienė, Daiva; Griškevičius, Algirdas (Transport, 2003)
To determine the demand for public transport on the market, a survey was conducted in 2001–2002 concerning the situation in the suburban zones of newly-built up districts where public transport is either inaccessible or poorly developed. The analysis was based on major social and economic factors determining the demand for transport. They are: demographic structure and development, restructuring of productive forces and space planning; employment and unemployment; income and poverty; social insurance, pensions and welfare; the household structure; income and expenditures; mobility of the inhabitants and motorization. The accessibility of transport services to passengers and the choice of transport facilities is closely related to their purchasing power. The offer of public transport services is lower than the demand, especially in the suburbs. As a result, the competition of automobiles is very strong there: the preference given to a car is determined by inaccessibility of public transport on the route for 22% of the inhabitants, while for 20% the reason was long way to a bus stop or large intervals in the schedule of public transport facilities. Based on the results obtained, the public transport system in Vilnius should be developed along three main lines: 1) raising the quality of public transport provided on fixed routes; 2) revising and updating the system of fares; 3) integrating the suburban public transport system into the central city transport system. These are the priority tasks associated with general goals of improving the system of public transport so that it could satisfy the needs of the passengers in the city.First Published Online: 19 Dec 2011